THE IMPORTANCE OF FOREIGN LANGUAGES IN BUSINESS - Islomova Gulyoraxon (University Research Base, 2024)
English is being used for more purposes than ever. It is closely related to economic modernization and industrial development. Companies compete fiercely for customers, while employees compete with each other for their own baan.de students' access to the professional language environment certainly contributes to its intensification. Foreign languages, especially many of these special, refer to international words. In order to teach and form students' interest in the topic of "foreign language", the teacher should not interfere in the motivational field of students, but learn to master it.